An Overview of Higher Education in India: Issues and Challenges - Dr. Anupa Singh (International Journal of Engineering and Management Research, 2018)
Education is the backbone of a progressive nation. Indian higher education system is the third largest in the world, next to United States and China. Since independence, India’s higher education sector has witnessed a tremendous increase in the number of Universities/University level institutions and Colleges. Their role in the present time is to provide quality based education and research to empower youth for self-sustainability. However this sector is facing many challenges like financing and management including access, equity and relevance, reorientation of programmes by laying emphasis on values, ethics and quality of higher education and research. It needs greater transparency and accountability, the role of colleges and universities in the new millennium. India needs well skilled and highly educated people who can drive our economy forward. This paper aims to give an overview of higher education in India, the key issues and challenges it is facing and also suggestions for improving the higher education system.